DESAIN SARANA DAN PRASARANA EDU-EKOWISATA MANGROVE DI BULAKSETRA, KABUPATEN PANGANDARAN - Indra Kristiana; Kennedi Sembiring; Mario Pandu Wiranata (Journal of Aquatropica Asia, 2020)
Mangrove ecosystems in coastal areas play an important role in supporting physical, biological, and environmental economic functions. One of the alternatives to preserve the mangrove ecosystem is integrated area management. Bulaksetra Beach is a mangrove area located on the East Coast of Pangandaran which has the potential to be developed as an ecotourism area. The Edu-ecotourism area which combines conservation, education, research, and economy requires good and appropriate management. Analysis of land suitability, vegetation types and environmental conditions is important in making decisions and determining the feasibility of an area. Facilities and infrastructure are one of the elements and indicators that support the success of an Edu-ecotourism area. Observations on water conditions, types of mangrove vegetation, water substrate, weather and topography were carried out to determine the feasibility of developing facilities and infrastructure in the Bulaksetra area. The results showed that the Bulaksetra area was feasible to be developed into an Edu-ecotourism area with an average salinity measurement of 14 ppt, an average rainfall of 46.4 mm - 81.3 mm, a sandy mud substrate and a gentle topography. The zoning of the mangrove ecosystem was carried out based on the main mangrove vegetation in Bulaksetra, namely Avicennia alba and Rhizophora apiculata. The selection of vegetation in the landscape design is adjusted to the natural vegetation and topography in the Bulaksetra area. The supporting facilities for Bulaksetra Edu-ecotourism were designed include mangrove trekking, canoeing docks and mangrove galleries. Facilities are designed according to area size, landscape, and suitability of location. Further studies such as the selection of design and building materials, material costs, construction costs, operational costs and maintenance costs need to be carried out to determine the appropriate building construction. The development of Bulaksetra Edu-ecotourism facilities and infrastructure is expected to contribute to the development of the mangrove ecosystem so that it becomes a center for information, education, and conservation for the public, especially in Pangandaran Regency.